CFD Study on The Effort of Lowering Construction Height of The Upper Part Cement Preheater - Gusti Putu Firman Hadi, I
Suspension Preheater is a part of cement plant equipment to enhance kiln feed temperature up to 800-9000C with 80-90% calcination degree. The problem occured on the suspension preheater design is the high elevation of cantilever construction needed to support overall structure. Suspension preheater structure could reach 100 m altitude thereby increasing construction and operation cost. This study is intended to support efforts reducing the suspension preheater structure height in order to decrease construction investment costs and operating expenses in kiln feed transport. This study consist of the upper part of the suspension preheater cement plant with 8000 tons per day capacity on ILC string (In Line Calciner). Thermal and fluid performance were evaluated with CFD (Computational Fluid Dynamics) simulation and would be used as criteria in assessing the success of the proposed design. Overall heat transfer coefficient between hot gas and kiln feed particles while in the suspension preheater will be evaluated as additional performance criteria. From this research, it could be concluded that the height of the upper part of the suspension preheater likely to be reduced up to 26.39%, while the energy to lift and transport the kiln feed is also likely to be lowered 16.67% even though the ID fan work would have to increase by 8.25%, while maintaining same thermal performance and production process currently used widely in cement plants.